2017
DOI: 10.1016/j.sleep.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Allostatic load in early pregnancy is associated with poor sleep quality

Abstract: Background Allostatic load (AL) measures the cumulative impact of chronic stress and is associated with adverse health outcomes. A novel scoring system has previously been developed for AL in early pregnancy that is associated with pre-eclampsia. It was hypothesized that AL, as identified by the present model, is associated with psychosocial stressors and, specifically, poor sleep quality. Methods Women were selected from a low-risk, community-dwelling study population who enrolled at <15 weeks gestation. Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Allostatic load was associated with healthdamaging lifestyle habits, such as lack of physical activity, unhealthy diet and poor sleep, in several investigations [52,228,229,233,239]. The metabolic syndrome, which may be fre quently associated with allostatic load [17], is an important example of the devastating effects of harmful lifestyles and of the need to prevent its occurrence as early as possible in life [314].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Allostatic load was associated with healthdamaging lifestyle habits, such as lack of physical activity, unhealthy diet and poor sleep, in several investigations [52,228,229,233,239]. The metabolic syndrome, which may be fre quently associated with allostatic load [17], is an important example of the devastating effects of harmful lifestyles and of the need to prevent its occurrence as early as possible in life [314].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed a significant association be tween depressive and anxiety symptoms and allostatic Psychother Psychosom 2021;90:11-27 DOI: 10.1159/000510696 load [279][280][281][282][283], not confirmed by others [233,[284][285][286]. In the association between childhood physical abuse and depression in adulthood, allostatic load appeared to have a mediating role [287].…”
Section: Mood and Anxiety Disordersmentioning
confidence: 98%
See 1 more Smart Citation
“…Understanding sleep patterns during pregnancy may have significant impacts on gestational outcomes [17]. During pregnancy, poor quality of sleep (PQOS) and sleep disorders have been associated with hypertensive states like preeclampsia (Preeclampsia can occur as early as 20 weeks of gestation, if one is at risk than symptoms usually occurs around 34th week) [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Sleep is gaining recognition as an important factor to consider when studying or treating pregnant women. For example, many epidemiological reports have linked poor sleep or insomnia to poor health outcomes, including depression (Okun, Kiewra, Luther, Wisniewski, & Wisner, 2011;Okun, Kiewra, Luther, et al, 2011;Volkovich, Tikotzky, & Manber, 2016;Wolynczyk-Gmaj et al, 2017;Yang et al, 2017;Hux, Roberts, & Okun, 2017), preterm birth (Okun, Luther, Prather, et al, 2011;Blair, Porter, Leblebicioglu, & Christian, 2015;Li et al, 2016) and longer labor times (Evans, Dick, & Clark, 1995;Lee & Gay, 2004). The undisputed association between stress and sleep is particulary poignant in pregnancy, as stress is independently associated with poor pregnancy outcomes (Okun, Roberts, Begley, Catov, & Patrick, 2013;Palagini et al, 2014;Hux et al, 2017).…”
Section: Overview Of Sleepmentioning
confidence: 99%